Digital Collaboration-Based Public Service Transformation Through The Ula Application - Sammy Andro Masengi (Journal Research of Social Science, Economics, and Management, 2025)
Public service transformation in the digital era requires strengthened interdepartmental collaboration supported by information technology. This study examines the implementation of the Administrative Service Unit (ULA) Application at the General Bureau of the North Sulawesi Provincial Secretariat as a form of digital collaboration to enhance the effectiveness of internal administrative services. Using a descriptive qualitative approach through document analysis, literature review, and limited administrative observation, this article explores how administrative digitalization accelerates workflows, establishes new collaborative patterns, and strengthens bureaucratic transparency. The findings indicate that ULA improves processing efficiency by approximately 40%, clarifies correspondence flows through digital audit trails, and strengthens inter-unit collaboration through an integrated work system. Digitalization also fosters a shift in bureaucratic culture toward more responsive, accountable, and network-based work patterns. These results demonstrate that digital collaboration is a strategic element in public service transformation within regional government settings.